PSYCHOLOGICAL DISTRESS ON CHILDHOOD CANCER: A CONCEPT ANALYSIS - Siti Arifah; Kanaungnit Pongthavornkamol (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2019)
This concept analysis is to clarify the psychological distress in term of pediatric cancer care. The literature review conducted to defining the antecedents, attributes and consequences of psychological distress analysed by Walker and Avent's theory. The finding were different components of antecedents and attributes, while the consequences was only negative.